Study on the impact of biofilm formation by Candida albicans in recurrent vulvovaginal candidiasis on drug susceptibility - Li, Sainan; Shen, Zijia; Wang, Suke; Peng, Yongmei; Qi, Wenjin (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundVulvovaginal candidiasis (VVC) and recurrent VVC (RVVC) are common fungal infections in women, often complicated by recurrence and treatment resistance. This study explores how Candida albicans biofilm formation influences antifungal susceptibility and resistance gene expression in clinical isolates.MethodsClinical Candida albicans isolates were collected and identified. Biofilm formation ability was assessed using crystal violet staining and confocal laser scanning microscopy. Based on the strength of biofilm formation, isolates from VVC and RVVC patients were categorized into three groups: strong positive, moderate positive, and weak positive. The antifungal susceptibility of each strain to fluconazole, flucytosine, clotrimazole, and amphotericin B was determined using a modified broth microdilution method. The expression levels of the drug efflux pump genes CDR1, CDR2, and MDR1 were measured before and after biofilm formation in each group using RT-qPCR.ResultsA higher proportion of strong biofilm-forming Candida albicans strains was of Candida albicans served in the RVVC group, whereas biofilm-negative strains were less common. In the VVC group, weak biofilm-formers produced significantly thinner biofilms than strong biofilm-formers in both VVC and RVVC (p<0.05). In RVVC weak biofilm-formers, amphotericin B exhibited higher MIC values than fluconazole and flucytosine (p<0.05), and across all RVVC subgroups, amphotericin B MICs were higher than those of clotrimazole (p<0.05). The MBEC of flucytosine was highest in the strongly positive VVC subgroup (p<0.05). In VVC, clotrimazole MBEC was lower in weak than in strong biofilm-formers (p<0.05). In RVVC, fluconazole MBEC was higher than flucytosine and clotrimazole in weak biofilm-formers, and also higher than amphotericin B in both weak and moderate biofilm-formers (p<0.05). Multivariate analysis further suggested that stronger biofilm-forming ability tended to increase the risk of RVVC independently of age, although this association did not reach statistical significance.ConclusionsStronger biofilm-forming Candida albicans strains showed higher MBEC values. In RVVC, clotrimazole had the lowest MIC and MBEC, supporting its potential as a first-line treatment. Expression of CDR1 and CDR2 was highest in strong biofilm-forming strains, suggesting that biofilm formation promotes antifungal resistance through enhanced efflux gene expression, especially in RVVC.